1993
DOI: 10.1128/mcb.13.12.7725-7733.1993
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the L-Type Pyruvate Kinase Gene Glucose Response Complex

Abstract: L-type pyruvate kinase (L-PK) gene expression is modulated by hormonal and nutritional conditions. We have previously shown that the glucose/insulin response element (GlRE) of the L-PK gene is built around two noncanonical E boxes (element L4) that cooperate closely with a contiguous binding site (element L3). We present in this report the identification of proteins that interact with both elements. The L3 site binds hepatocyte nuclear factor 4 (HNF4)- and COUP/TF-related proteins. In fibroblasts, the overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…This finding is interesting in light of previous observations showing that ARP-1 and EAR-3, when bound to proximal element B, repress the apoCIII promoter (Ladias et al, 1992;Myetus-Snyder et al, 1992). In addition, studies on several other promoters, including apoB, apoA-I, apoA-II, apoA-IV (Ladias et al, 1992;Ktistaki et al, 1994), L-type pyruvate kinase (Guerra et al, 1993), ornithine transcarbamylase (Kimura et al, 1993), and the cellular retinol binding protein (Nakshatri et al, 1994), showed that these factors modulate transcription in a negative direction. Although repressor activity of a transcription factor can be achieved by several different mechanisms, it is well-documented that in all cases when ARP-1 and EAR-3 act as repressors the negative effect is being exerted by competition with HNF-4 or other nuclear hormone receptors for the same binding site (Ladias et al, 1992).…”
Section: Potential Contribution Of Orphan Receptors Bound Tosupporting
confidence: 61%
See 1 more Smart Citation
“…This finding is interesting in light of previous observations showing that ARP-1 and EAR-3, when bound to proximal element B, repress the apoCIII promoter (Ladias et al, 1992;Myetus-Snyder et al, 1992). In addition, studies on several other promoters, including apoB, apoA-I, apoA-II, apoA-IV (Ladias et al, 1992;Ktistaki et al, 1994), L-type pyruvate kinase (Guerra et al, 1993), ornithine transcarbamylase (Kimura et al, 1993), and the cellular retinol binding protein (Nakshatri et al, 1994), showed that these factors modulate transcription in a negative direction. Although repressor activity of a transcription factor can be achieved by several different mechanisms, it is well-documented that in all cases when ARP-1 and EAR-3 act as repressors the negative effect is being exerted by competition with HNF-4 or other nuclear hormone receptors for the same binding site (Ladias et al, 1992).…”
Section: Potential Contribution Of Orphan Receptors Bound Tosupporting
confidence: 61%
“…Recent studies indicate that HNF-4 can synergize with a wide variety of transcription factors including C/EBP (Metzger et al, 1993), CREB (Nitsch et al, 1993), and HNF-1 (Guerra et al, 1993). This is reminiscent of the derivatives of the yeast activator GAL4, which can stimulate transcription in synergy with various mammalian transcription factors such as the glucocorticoid receptor, ATF, and USF (Carey et al, 1990;Lin et al, 1988Lin et al, , 1990.…”
Section: Discussionmentioning
confidence: 99%